The role of parathyroid hormone and cardiac output in pulmonary hypertension in hemodialysis patients - Sayyed golamreza Mortazavi Moghaddam; Nahid Azdaki; Mina Golgoon; Abbas ali Ramazani; Zainab Saremi (Journal of Nephropathology, 2020)
Introduction: High prevalence of pulmonary hypertension has been reported in patients with chronic renal failure, especially those undergoing hemodialysis. Objectives: Considering the high prevalence of pulmonary hypertension in hemodialysis patients and uncertainty about the causes, the present study planned to investigate the role of parathyroid hormone (PTH) and cardiac ejection fraction (EF %) in development of pulmonary hypertension. Patients and Methods: By simple census sampling, all patients on hemodialysis in the hemodialysis center of Birjand University of Medical Sciences were enrolled. After obtaining written consent, the EF% and systolic pulmonary artery pressure (sPAP) were determined using echocardiography (MEDISON V10 model, Korea). The cut-point of less than 35 mm Hg was considered for normal sPAP. The blood sample was prepared to assay PTH using COBAS411 and ROCH kit. Independent t test or Man-Whitney test were used to compare means. P value <0.05 was considered significant. Results: A totsl of 114 patients were enrolled in the study. Finally 89 patients, including 49 (55.1%) male and 40 (44.9%) female completed the study. The mean age and mean sPAP of the studied patients were 55.14 ± 15.68 years and 30.65 ± 12.10 mm Hg respectively. Among the studied patients, normal and high sPAP were reported in 60 (67.4%) and 29 (32.6%) cases respectively. Cardiac EF% in patients with normal and high sPAP was 59.08 ± 2.83 versus 56.37 ± 4.79 respectively (P = 0.01). PTH was determined 275.12 ± 218.44 versus 395.67 ± 332.05(pg/mL) (P = 0.03), in patients with normal and high sPAP respectively. Conclusion: The prevalence of pulmonary hypertension in the studied patients was 32.6%. Patients in the pulmonary hypertension group had higher levels of PTH and lower cardiac EF%.